2012
DOI: 10.2174/1874613601206010029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Blacks with HIV/AIDS in the United States: A Systematic Review of the Literature

Abstract: Objectives: Blacks in the United States bear a disproportionate burden of Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) and cardiovascular disease (CVD). It has been demonstrated that HIV/AIDS itself and HIV/AIDS-related therapies may predispose patients to early onset of CVD. It is also possible that Black patients may be at greater risk for this interaction. Thus, the objective of this literature review was to identify and critically evaluate disparities in CVD between Black a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(36 reference statements)
0
10
1
Order By: Relevance
“…However, the results of our study underscore the importance of addressing CVD risk factors in this demographic group. [2,45,46] Although gender was not a significant predictor of CVD in our cohort, other studies have shown that HIV-positive females have a significantly higher risk of CVD compared with seronegative females. [47][48][49] Some studies have demonstrated associations between ARTs and increased CVD risk.…”
Section: Discussioncontrasting
confidence: 78%
“…However, the results of our study underscore the importance of addressing CVD risk factors in this demographic group. [2,45,46] Although gender was not a significant predictor of CVD in our cohort, other studies have shown that HIV-positive females have a significantly higher risk of CVD compared with seronegative females. [47][48][49] Some studies have demonstrated associations between ARTs and increased CVD risk.…”
Section: Discussioncontrasting
confidence: 78%
“…In a systemic review of African Americans with HIV/AIDS in the United States, 2 of 5 studies indicated that African Americans with HIV were at increased CVD risk. 154 One of the few large assessments of CVD in African Americans with HIV is derived from a retrospective analysis of US National Hospital Discharge Surveys (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) showing that of 1.5 million discharges, the likelihood of hospitalization for CVD conditions was almost 50% higher (OR, 1.45; 95% CI, 1.39-1.51) in African Americans than in whites. 155 However, an unexpected observation that warrants further investigation is that, when the subclinical coronary artery disease burden was compared between African American men with and without HIV in MACS (Multicenter AIDS Cohort Study), HIV positivity was associated with lower volume of total plaque.…”
Section: Hiv/aidsmentioning
confidence: 99%
“…Reports from cohort studies and clinical trials indicate that neurocognitive performance of HIV patients with CVD risk factors is impaired [ 3 , 10 , 103 , 131 , 133 135 ]. HIV is disproportionately represented among African Americans and Latinos, who also bear a greater burden of CVD, as compared to other ethnic groups [ 136 – 138 ]. Compounded with the unfortunate realities of later presentation for care and lower rates of virologic control, the risk for vascular-associated neurocognitive disorders in these populations is greater [ 139 141 ].…”
Section: Physical Comorbidities Effecting Cognitionmentioning
confidence: 99%